The Role of Decompressive Craniectomy in the Context of Severe Traumatic Brain Injury: Summary of Results and Analysis of the Confidence Level of Conclusions From Systematic Reviews and Meta-Analyses - Rubiano, Andrés M.; Carney, Nancy; Khan, Ahsan A.; Ammirati, Mario (Frontiers in Neurology, 2019)
Traumatic brain injury is a worldwide public health problem. The burden is bigger in low and middle-income countries. Decompressive craniectomy has been used as a common intervention for the treatment of these patients. There are different opinions from the results of the clinical studies evaluating the impact of the intervention. This review will discuss the role of the procedure in severe TBI. Five systematic reviews published between 2006 and 2016 and the only three Class 1 randomized control trials published until now were analyzed. Four systematic reviews have important methodological flaws and one was outdated and did not include the most recent Class 1 trials in the analysis of the intervention´s evidence. The only pediatric trial shows benefit of the intervention. The first adult trial does not find any benefit of the surgical procedure compared with medical management and the most recent adult trial shows improving of survival but with increases of disability in short term. Generalizability and transferability of the results of these studies need to be carefully analyzed in order to bring these results to the daily bases decision-making process in different regions of the world. Analysis of these studies deserves a careful examination of the variables involved on each one of the studies, specially the mechanisms behind formulating the causal model for the conclusions. These findings does not mean we will abandoned the procedure but rather means we need to improve the selection of cases that can be beneficiated from the intervention. Special attention of ethical considerations and minimization of bias for further studies will allow to fine tune the criteria to perform DC, both primary and secondary, in a more selective way, taking into account the different socioeconomic and cultural contexts.